2008
DOI: 10.1002/cncr.23921
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial of lipoplatin and gemcitabine as a second‐line chemotherapy in patients with nonsmall cell lung carcinoma

Abstract: BACKGROUND.Lipoplatin is a new liposomal cisplatin that already has been tested in solid tumors, with encouraging results. The purpose of the current study was to determine the maximum tolerated dose (MTD) and the dose‐limiting toxicity (DLT) of a 21‒day regimen of lipoplatin plus a fixed dose of gemcitabine in patients with refractory or resistant nonsmall cell lung carcinoma (NSCLC) with an Eastern Cooperative Oncology Group (ECOG) performance status of ≤2.METHODS.The lipoplatin dose was escalated at 100 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Total platinum concentrations were determined in plasma using a GF-AAS (Graphite Furnace Atomic Absorption Spectrometry) assay using an Ati-Unicam model 939QZ, as previously described [14,18]. The quantification limit was 0.02 g/ml and the detection limit was 0.01 g/ml.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Total platinum concentrations were determined in plasma using a GF-AAS (Graphite Furnace Atomic Absorption Spectrometry) assay using an Ati-Unicam model 939QZ, as previously described [14,18]. The quantification limit was 0.02 g/ml and the detection limit was 0.01 g/ml.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…Preclinical studies on lipoplatin showed a low toxicity profile, an ability to concentrate in tumors and to escape immune cells and macrophages, a slow clearance rate from the kidneys, long circulation properties in body fluids, a half-life of 36 h in the blood, and promising therapeutic efficacy [11]. Phase I studies of lipoplatin alone [13] or in combination with antimetabolites [14] showed efficacy in patients with solid tumors and an excellent toxicity profile. This compound has also shown activity and low toxicity in association with gemcitabine in pleural and peritoneal mesothelioma [15].…”
Section: Introductionmentioning
confidence: 97%
“…In this study, the highest platinum levels among all tissues examined were found in gastric cancer specimens, most likely reflecting the high degree of vascularization of these tumors and the ability of the nanoparticle formulation for extravasation through the compromised endothelium of the tumor (17). In a Phase I trial performed at our institution in lung cancer patients, Froudarakis et al suggested that the maximum tolerated dose of Lipoplatin, when given together with gemcitabin, is 120 mg/m 2 for two weekly cycles, repeated every 21 days (12). Based on the above data, we postulated that Lipoplatin represents a candidate drug to test its activity together with radiation.…”
Section: Discussionmentioning
confidence: 94%
“…5-Fluorouracil (400 mg/m 2 ), leucovorin (200 mg flat dose), and Lipoplatin (120 mg/m 2 ) were administered on day 1 of each week. The choice of the Lipoplatin dose was based on the previous experience from our institute on a Phase II trial in lung cancer (12). Lipoplatin was diluted in 1L of D/W (dextrose 5% in water) and was administered as a 3 h infusion at an outpatient basis.…”
Section: Chemotherapy Regimenmentioning
confidence: 99%
“…Pharmacokinetics, safety and efficacy were studied in several phase I and II studies [37][38][39][40][41]; halflife was shown to be between 30 and 50 h depending on the dose, in comparison to 6 h for cisplatin. There was no need for pre-or posthydration during Lipoplatin administration contrary to cisplatin.…”
Section: Introductionmentioning
confidence: 99%